New red blood cell and reticulocyte parameters and reference values for healthy individuals and in chronic kidney disease - Patrícia S. Scherer; Daniela Moraes; Terezinha P. Munhoz; Vanessa Sgnaolin (Sociedade Brasileira de Patologia Clínica, 2015)
Introduction: The importance of local references values has been well described in the literature; this is because the characteristics of the population may influence the laboratory tests. Objective: To establish the reference range for traditional and extended red blood cell parameters and reticulocyte indices in order to investigate its application in patients with chronic kidney disease (CKD). Materials and methods: 249 blood donors (125 males and 124 females) were selected to establish the reference values. The hemodialysis sample consisted of 62 patients with terminal CKD (48 male and 14 female). All analyzes were performed using the Sysmex XE-5000 automated hematology analyzer. Results: Differences between reference values was observed in relation to gender: red blood cells (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular hemoglobin concentration (MCHC), percentage of hyperchromic red blood cells (%HYPER), percentage of microcytosis (%MICRO), percentage of macrocytosis (%MACRO), absolute reticulocyte count (RET), reticulocyte hemoglobin content (RET-He), immature reticulocyte fraction (IFR), low fluorescence reticulocytes (LFR), medium fluorescence reticulocytes (MFR), and high fluorescence reticulocytes (HFR). Individuals with CKD presented RBC, HGB, HCT, MCHC, red cell distribution width expressed as coefficient of variation (RDW-CV), percentage of hypochromic red blood cells (%HYPO), percentage of reticulocytes (RET%), RET (female group), IFR, LFR, MFR, and HFR results compatible with the anemic state, which can be observed in 91.8% of patients. All studied parameters were in the area under the curve (AUC) > 0.4. In male group, %HYPO (AUC: 0.806) and IFR (AUC: 0.762) presented higher AUC values, while female group presented %HYPO (AUC: 0.806), %HYPER (AUC: 0.815), and IFR (AUC: 0.660). Conclusion: The medical advancement, the development of new techniques and hematological parameters have revealed important information about functional integrity of bone marrow, diagnosis of anemia and recombinant human erythropoietin monitoring therapy used in hemodialysis patients.